Optimalisasi Kompetensi Pegawai dalam Analisis Kredit dan Manajemen Risiko pada Credit Union - Hartono, Hartono; Indah, Nopiani (JPM: Jurnal Pengabdian Masyarakat, 2026)
This community engagement activity was implemented at Credit Union (CU) Muara Kasih Pontianak, a member-based microfinance institution that plays a vital role in community economic empowerment, particularly the Micro, Small, and Medium Enterprises (MSME) sector. CU Muara Kasih faces challenges in loan disbursement amid competition and a difficult economic situation. Based on observations, there were still loans categorized as non-performing (NPLs), indicating the necessity for enhancing human resource capacity in credit risk management. The purpose of this community service program is to enhance the competence of employees of Credit Union (CU) Muara Kasih Pontianak in credit analysis and credit risk management as an effort to optimize lending effectiveness and reduce non-performing loans. The activity was conducted over two days in October 2024 and involved all seven CU employees. The methods employed included interactive lectures, case studies based on real data, a simple credit scoring simulation, and mentoring for the development of a standardized credit analysis template. Evaluation results showed a significant improvement in participants' technical abilities in performing credit analysis and risk identification, with an average post-test score increase of 60.6% compared to the pre-test. Furthermore, the CU began implementing an integrated credit analysis template and a spreadsheet-based quarterly financial performance audit system. The impact of this activity was evident in the increased efficiency of credit reporting, transparency in the evaluation process, and enhanced employee competency within the three-month post-training period. This initiative also strengthened member trust in CU Muara Kasih and serves as a model for implementing collaborative learning between academics and microfinance institutions to improve member financial literacy.